2021
DOI: 10.3389/fnins.2021.653470
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila melanogaster Levodopa-Induced Depression Model Exhibits Negative Geotaxis Deficits and Differential Gene Expression in Males and Females

Abstract: More than 320 million people live with depression in the world, a disorder that severely limits psychosocial functioning and diminishes quality of life. The prevalence of major depression is almost two times higher in women than in men. However, the molecular mechanisms of its sex-specific pathophysiology are still poorly understood. Drosophila melanogaster is an established model for neurobiological research of depression-like states, as well as for the study of molecular and genetic sex differences in the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Negative geotaxis in flies is the innate motivation to climb vertically when startled; impairment in this response has been observed in flies with lower serotonin and octopamine levels, 32 which are associated with a depression-like state in flies. 15,33 While it is possible that impaired climbing behavior in this study was related to decreased endurance, previous studies in Drosophila have shown that depression does not cause diminished general activity. 15 Studies have consistently shown that depressed individuals have altered sleep-wake cycles, but it is not clear if depression precedes altered sleep or vice versa.…”
Section: Circadian Dysfunction Sleep Disturbance and Moodmentioning
confidence: 75%
“…Negative geotaxis in flies is the innate motivation to climb vertically when startled; impairment in this response has been observed in flies with lower serotonin and octopamine levels, 32 which are associated with a depression-like state in flies. 15,33 While it is possible that impaired climbing behavior in this study was related to decreased endurance, previous studies in Drosophila have shown that depression does not cause diminished general activity. 15 Studies have consistently shown that depressed individuals have altered sleep-wake cycles, but it is not clear if depression precedes altered sleep or vice versa.…”
Section: Circadian Dysfunction Sleep Disturbance and Moodmentioning
confidence: 75%
“…Next, we sought to further characterize the nature of the immediate movement response to lights-off stimuli. As it has been shown that male and female flies can differ in many light-related behaviors, including daily activity and motion responses [ 38 , 39 , 40 ], we separated males and females from our sample ( Figure 1 D) and assessed if there were sex variations in the startle index ( Figure 2 A). Two-way ANOVA showed no significant difference among male and female responses ( p = 0.985).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we previously demonstrated that fluvastatin treatment for five days reduces the mean activities and promoted sleep duration [ 55 ]. Therefore, we examined the effect of fluvastatin on the climbing ability and general locomotion activity using wild-type CSORC flies as they are commonly used in locomotion and climbing assays [ 61 , 71 ]. We employed the Drosophila Activity Monitoring System (DAMS) for monitoring general locomotion activities and improved the Forced-Climbing System described by Moulin et al [ 61 ] to record different aspects of fly climbing ability including the hourly average of moves, speed and positions (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the effect of fluvastatin on the climbing ability of the flies, we used the Forced-Climbing System as described by Moulin et al [ 61 ]. In short, this system comprises two MultiBeam Activity Monitor, MB, (TriKinetics Inc., Waltham, MA, USA) placed vertically in Vortexer Mounting Plate, VMP, (TriKinetics Inc., Waltham, MA, USA) see Figure 1 .…”
Section: Methodsmentioning
confidence: 99%